Understanding Antibiotic Residues and Pathogens Flow in Wastewater from Smallholder Pig Farms to Agriculture Field in Ha Nam Province, Vietnam. (September 2020) - Pham-Duc, Phuc; Nguyen-Viet, Hung; Luu-Quoc, Toan; Cook, Meghan A; Trinh-Thi-Minh, Phuong; Payne, Dave; Dao-Thu, Trang; Grace, Delia; Dang-Xuan, Sinh
Background: Contact with livestock wastewater on farms and in communities can pose a risk to human and animal health. Methods: This cross-sectional study was conducted in 180 households and 24 pig farms (96 wastewater samples) to explore information about pig production, livestock waste management, antibiotic use, and to analyze antibiotic residues and microbial contamination, respectively. Results: Of the 120 households raising pigs, biogas systems were the most commonly used to treat animal waste (70%), followed by compositing (19%), and the remaining respondents discharged waste directly into drains or ponds (11%). The majority of respondents (78%) used antibiotics to treat and prevent disease in pigs, but 32% of them did not know of any disadvantages of antibiotic abuse. ELISA assays were performed on half of the wastewater samples (n = 48), demonstrating that residues of flouroquinolones and sulfonamides were present in 6.3% (3/48) and 22.9% (11/48) of tested samples, respectively. The average residual level of sulfamethazine was 27.8 ug/l. Further, E. coli concentrations exceeding regulatory levels in Vietnam were found in nearly all samples. Salmonella spp. was also found in 57.3% of samples, though prevalence rates varied across the different sites. Finally, G. lamblia was found in 8.4% of samples, and C. parvum was found in 5.2% of samples. Conclusions: This study suggests that livestock wastewater carried potential harmful pathogens and antibiotic residues that could come into contact with humans in the community. Thus, appropriate operation and application of livestock wastewater treatment (such as biogas or composting) and management should be a continued focused.